Published criteria for evaluating health related web sites: review - Kim, Paul (British Medical Journal, 1999)
OBJECTIVE: To review published criteria for specifically evaluating health related information on the world wide web, and to identify areas of consensus. DESIGN: Search of world wide web sites and peer reviewed medical journals for explicit criteria for evaluating health related information on the web, using Medline and Lexis-Nexis databases, and the following internet search engines: Yahoo!, Excite, Altavista, Webcrawler, HotBot, Infoseek, Magellan Internet Guide, and Lycos. Criteria were extracted and grouped into categories. RESULTS: 29 published rating tools and journal articles were identified that had explicit criteria for assessing health related web sites. Of the 165 criteria extracted from these tools and articles, 132 (80%) were grouped under one of 12 specific categories and 33 (20%) were grouped as miscellaneous because they lacked specificity or were unique. The most frequently cited criteria were those dealing with content, design and aesthetics of site, disclosure of authors, sponsors, or developers, currency of information (includes frequency of update, freshness, maintenance of site), authority of source, ease of use, and accessibility and availability. CONCLUSIONS: Results suggest that many authors agree on key criteria for evaluating health related web sites, and that efforts to develop consensus criteria may be helpful. The next step is to identify and assess a clear, simple set of consensus criteria that the general public can understand and use.